Armiero, Marco, (2021). Wasteocene. Stories from the Global Dump - Boric, Irena (Journal of Ecohumanism, 2022)
Armiero, Marco, (2021). Wasteocene. Stories from the Global Dump. Cambridge Elements. Elements in Environmental Humanities, Cambridge University Press. ISBN: 978-1-108-82674-7.